Evaluation of nuclear material accountability by the probability of detection for loss of Pu (LOPu) scenarios in pyroprocessing - Woo, Seung Min; Chirayath, Sunil S. (Nuclear engineering and technology, 2019)
A new methodology to analyze the nuclear material accountability for pyroprocessing system is developed. The Pu-to-244Cm ratio quantification is one of the methods for Pu accountancy in pyroprocessing. However, an uncertainty in the Pu-to-244Cm ratio due to the non-uniform composition in used fuel assemblies can affect the accountancy of Pu. A random variable, LOPu, is developed to analyze the probability of detection for Pu diversion of hypothetical scenarios at a pyroprocessing facility considering the uncertainty in Pu-to-244Cm ratio estimation. The analysis is carried out by the hypothesis testing and the event tree method. The probability of detection for diversion of 8 kg Pu is found to be less than 95% if a large size granule consisting of small size particles gets sampled for measurements. To increase the probability of detection more than 95%, first, a new Material Balance Area (MBA) structure consisting of more number of Key Measurement Points (KMPs) is designed. This multiple KMP-measurement for the MBA shows the probability of detection for 8 kg Pu diversion is greater than 96%. Increasing the granule sample number from one to ten also shows the probability of detection is greater than 95% in the most ranges for granule and powder sizes. Keywords: Safeguards, Nuclear material accountancy, Pyroprocessing, Probability of detection, Loss of Pu, Nuclear material diversion, SERPENT